2005
DOI: 10.1007/s11259-005-4682-x
|View full text |Cite
|
Sign up to set email alerts
|

Status of Lipid Peroxidation, Some Antioxidant Enzymes and Erythrocytic Fragility of Crossbred Cattle Naturally Infected with Theileria annulata

Abstract: Erythrocytic lipid peroxidation, activities of some antioxidant enzymes and osmotic fragility of red blood cells was studied in adult (>1 year) crossbred cattle naturally infected with Theileria annulata. Twenty clinically healthy animals (group I) and 15 clinical cases (group II) of tropical theileriosis were selected. Cattle suffering from theileriosis had significantly higher (p<0.01) erythrocytic lipid peroxidation and osmotic fragility. Activities of antioxidant enzymes, viz. glucose-6-phosphate dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 10 publications
10
37
2
1
Order By: Relevance
“…Thus, it can be suggested that the invasion of RBCs by the parasites could markedly affect key antioxidant defense barriers, resulting in significant RBC damage and finally leading to extravascular hemolysis. Our data corroborate the previous studies on bovine tropical theileriosis (Rezaei and Dalir-Naghadeh, 2006;Nazifi et al, 2009), but Grewal et al (2005) reported that the GPX activity was significantly elevated whereas the enzymes SOD and catalase showed no remarkable changes in cattle infected with T. annulata. They concluded that the increased level of GPX during the infection could be due to the fact that this enzyme activity is the major mechanism for the intracellular destruction of lipid peroxides rather than SOD or catalase activity, while our findings showed that, parallel to the role of GPX, the activities of SOD and catalase could also be important factors for RBCs to scavenge the oxidant agents during the parasitemia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, it can be suggested that the invasion of RBCs by the parasites could markedly affect key antioxidant defense barriers, resulting in significant RBC damage and finally leading to extravascular hemolysis. Our data corroborate the previous studies on bovine tropical theileriosis (Rezaei and Dalir-Naghadeh, 2006;Nazifi et al, 2009), but Grewal et al (2005) reported that the GPX activity was significantly elevated whereas the enzymes SOD and catalase showed no remarkable changes in cattle infected with T. annulata. They concluded that the increased level of GPX during the infection could be due to the fact that this enzyme activity is the major mechanism for the intracellular destruction of lipid peroxides rather than SOD or catalase activity, while our findings showed that, parallel to the role of GPX, the activities of SOD and catalase could also be important factors for RBCs to scavenge the oxidant agents during the parasitemia.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, other studies have suggested that erythrocyte destruction during oxidative stress was related to lipid peroxidation of the RBCs (Friedman, 1979;Grewal et al, 2005). This process might be the cause of morphological changes in erythrocyte surface (Saluja et al, 1999;Grewal et al, 2005), which increase erythrocyte susceptibility to phagocytosis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lipid peroxidation in the RBC hemolysate was determined as thiobarbituric acid reactive substance (TBARS) according to Grewal et al (2005). The method is depended on forming a color complex between the products of lipid peroxidation and thiobarbituric acid (TBA).…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Research carried out in recent years demonstrates a relation between parasitic invasion and emergence of oxidative stress (Grewal et al 2005). A decrease in Cu and Zn content in the liver was reported by Dimri et al (2010) in sheep infested with Psoroptes ovis.…”
Section: Discussionmentioning
confidence: 84%